DISKRIMINASI KASTA TERHADAP PEREMPUAN BALI DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI - Nurdia, Hasnul; Gladis Candani, Anastasia; Uchie, Meldha; Elsa Nanta, Septiana; Sulastri, Saptiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The novel Tarian Bumi by Oka Rusmini (2000) reflects the caste system in Bali that marginalizes women through the levels of Brahmana, Kesatria, Vaisya, and Sudra. This study aims to reveal the forms and meanings of caste discrimination experienced by Balinese women, represented by the characters Luh Sekar (Jero Kenanga) and Ida Ayu Telaga, who are trapped in patriarchal norms and the tradition of nyerod (inter-caste marriage). The background of the problem arises from the conflict between ancient traditions that regulate marriage and social status, and the aspirations of women who want to achieve equality in a multicultural society in Indonesia. The method used is qualitative with a focus on content analysis of the novel text as the main object, accompanied by a literature study. Data collection was carried out through in-depth reading to identify the actions, dialogues, and representations of the Sudra and Brahmana characters. The analysis was carried out descriptively and systematically to group various forms of discrimination, such as social segregation, negative stereotypes, forced obedience, heavy workloads, and symbolic violence that occurs through the Patiwangi ceremony. This research shows that Sudra women who move up in caste are viewed as "formal servants" in Brahmin households, while marrying down results in ostracism and poverty. Luh Sekar fights to maintain her status, while Telaga's fight ends in tragedy: ridicule, her husband's death, and a ritual severance of ties with her family. This discrimination reinforces existing gender inequality.